Analisis Perbandingan Pendapatan Sebelum dan Setelah Menggunakan QRIS Di Pasar Seni To’pao, Kabupaten Toraja Utara - Pauline Surjadi Popang; Rati Pundissing; Mince Batara (Journal Economic Excellence Ibnu Sina, 2023)
Technology in the financial sector plays a crucial role in human life, as evidenced by the widespread use of electronic money. The advent of cashless payments, such as QRIS, can enhance financial management for businesses and contribute to their success. This research aims to compare the income of MSMEs before and after implementing QRIS in their operations. The sample size used in this study consists of 35 MSMEs at To’Pao Art Market, selected through saturation sampling. Data collection was conducted using a questionnaire, and data analysis was performed using the Paired t-Test. The results of this study indicate that there is a difference in MSMEs' income before and after the adoption of QRIS. This is supported by the Paired t-Test, which yielded a significance value (α) of less than 0.05 (0.007 < 0.05). The average income before using QRIS was 20.77, whereas after implementing QRIS, there was an increase in the average income to 21.60. Based on the results of the paired t-test, it can be concluded that the use of QRIS has a positive impact on MSMEs' income."